Treaty of Asuncion : an analysis. - Chatterjee, Charles (1992)
Examines the extent to which the Treaty of Asuncion is different from other similar treaties, and whether integration may be achieved in the Latin American region. Notes that the Common Market envisaged by this Treaty concerns primarily trade and investment.